TWENTY EIGHT YEARS OF ICP VEGETATION: AN OVERVIEW OF ITS ACTIVITIES - Harmens, H.; Mills, G.; Hayes, F.; Norris, D. A.; Sharps, K. (Annali di Botanica, 2015)
Here we look back at the activities and achievements in the 28 years of the International Cooperative Programme on the Effects of Air Pollution on Natural Vegetation and Crops (ICP Vegetation). The ICP Vegetation is a subsidiary body of the Working Group on Effects of the UNECE Convention on Long-range Transboundary Air Pollution (LTRAP), established in 1979. An important role of the ICP Vegetation is to provide evidence for air pollution impacts on vegetation in support of policy development and review of the LRTAP Convention and its Protocols. The activities and participation in the ICP Vegetation have grown over the years. The main activities include: Collate evidence of ozone impacts on vegetation, assess spatial patterns and temporal trends across Europe; Develop dose-response relationships, establish critical levels for vegetation and provide European risk maps of ozone impacts; Reviewing the literature on ozone impacts on vegetation and produce thematic scientific reports and policy-relevant brochures; Determine spatial patterns and temporal trends of heavy metals, nitrogen and persistent organic pollutants concentrations in mosses as a biomonitoring tool of atmospheric deposition of these compounds.